Discovery of the rare Mucor ardhlaengiktus (Mucorales, Mucoromycota) in South America - Dos Santos, Francisca Robervania Soares; da Cruz, Mateus Oliveira [UNESP]; Lima, Catarina Letícia Ferreira; Cordeiro, Thalline Rafhaella Leite; Dos Santos, Maria Alice Barbosa; de Freitas, Leslie Waren Silva; da Costa, Diogo Paes; Gurgel, Luciana Melo Sartori; Santiago, André Luiz Cabral Monteiro de Azevedo (Schweizerbart, 2023)
Mucor ardhlaengiktus is reported for the first time in South America, where it was isolated from soil in an upland rainforest area, located in the municipality of Sanharó, state of Pernam-buco, Brazil. The strain URM 8592 is characterized by forming simply branched sporangiophores, some monopodially branched, globose and subglobose columellae, infrequently ellipsoid with a slight constriction at the base. The sporangiospores are mostly ellipsoid, although some are ovoid, reniform and rarely irregularly shaped, and chlamydospores are frequently formed. This study pre-sents a detailed morphological description of this rare mucoralean fungus. Aspects of its taxonomy and geographical distribution are also commented.
Keywords: Mucoromycetes; Mucoromycotina; soil; taxonomy